Detectability of gas bubbles in blood by the ultrasonic method - FILIPCZYŃSKI, Leszek (Archives of Acoustics, 1983)
The reflection of a plane ultrasonic wave from a gas bubble in the blood was considered quantitatively in the range ka ≤ 1 (a is the radius of the bubble, k = 27π/λ and λ is the wavelength). Taking as an example the elbow vein (vena basilica), the losses in a signal caused by electroacoustical transducing, attenuation of the wave in tissues, reflection of the wave from the bubble and divergence of the reflected wave were evaluated using a typical ultrasonic Doppler device with a frequency of 8 MHz. It was shown that a single gas bubble with the radius 1.6 μm already gives a signal which is received by the device; this signal, however, is masked by the signal caused by the scattering of the wave by blood cells and, in addition, this bubble is instable. Determination of the level of signals scattered in blood indicated that in the case investigated it is possible to detect in the vein a single gas bubble with its radius greater than 16 μm or gas bubbles with a radius of 11 μm lying at the stability limit provided that their density exceeds 35 cm^-3. The present calculation procedure permits the determination in a specific anatomic case of the level of signals scattered by blood, the level of electronic noise and also the determination of the detectability of gas bubbles in blood caused, for example, by the decompression of divers or by the caisson disease. In the case of the pulmonary artery, using a frequency of 5 MHz, minimum radii of detectable gas bubbles greater than 70 μm were obtained.